PARAMETERS OF HIGH-TEMPERATURE CONDUCTIVITY OF ALPINE-TYPE DUNITE-HARZBURGITE ULTRAMAFIC ROCKS OF THE URALS AS A POSSIBLE GUIDE FOR THEIR POTENTIAL CHROMITE MINERALIZATION - Bakhterev V.V. (My University, 2006)
Numerous deposits and occurrences of high-quality chromites in the Urals are related to the Alpine-type dunite–harzburgite ultramafic rocks. The chromite ore mineralization is characterized by extremely complicate localization conditions and wide variability of typomorphic features. Diverse viewpoints on genesis and formation conditions of chromite mineralization do not allow unequivocal judgment on the potential of particular ultramafic massifs. The existing geophysical methods do not yield an adequate effect. The development of new methods for the forecasting and evaluation of chromite deposits is very topical. The study of high-temperature conductivity probably will allow us to elaborate new untraditional prospecting guides.
Keywords: Urals; chromite mineralization